Th17 cells and inflammation in neurological disorders: Possible mechanisms of action - Shi, Yajun; Wei, Bin; Li, Lingjun; Wang, Bin; Sun, Miao (Frontiers in Immunology, 2022)
Neurological disorders are the second leading cause of death worldwide. A sustained neuroinflammatory response is associated with the pathogenesis of many neurological disorders including Parkinson’s disease (PD), Alzheimer’s disease (AD), Multiple Sclerosis (MS), Amyotrophic lateral sclerosis (ALS) and Major depressive disorder (MDD). Emerging evidence shows that the recruitment of self-reactive lymphocytes in the central nervous system (CNS) may contribute to the development and progress of inflammation in neurological disorders. As one kind of self-reactive lymphocyte, CD4+ T cells play a vital role in the inflammation of neurological disorders. Distinct from Th1 and Th2 lymphocytes, T helper 17 (Th17) cells are the most studied CD4+ Th subpopulation that produce cytokines, such as IL-17A, IL-21, IL-23, IL-6, IFN-γ and granulocyte monocyte-colony stimulating factor (GM-CSF), leading to the abnormal neuroinflammatory response include the excessive activation of microglia and the recruitment of other immune cell types, all these together involved in the cause of several neurological disorders. However, the role of Th17 cells and their related cytokines in the immunopathology of inflammation in the above-mentioned neurological disorders have not been clarified completely. This review will summarize the mechanisms by which encephalitogenic inflammatory Th17 cells and their related cytokines strongly contribute to chronic neuroinflammation, thus perpetuating neurodegenerative processes in the disorders mentioned above. Finally, the approved, as well as the novel therapeutic prospects targeting Th17 cells and their related cytokines in neurological disorders will also be discussed.